Peak and valley regulation of distribution network with electric vehicles. Issue 16 (7th December 2018) - Li, Fucun; Guo, Hongxia; Jing, Zhen; Wang, Zhaojun; Wang, Xinku
Abstract : With the increasing number of electric vehicles (EVs), how to make full use of EVs to a peak shaving and valley filling effect on the electrical load, realise the effective interaction between EVs and power grid has become a hot spot of research. However, EV charging is random and uncertain on the characteristics of time and space, in this study, the authors consider the interaction between the EV and the power grid as the foraging behaviour of birds combined with the construction of EV charging station, and build a charge–discharge model based on a particle swarm optimisation algorithm to achieve optimal results through group cooperation. Finally, the feasibility of the scheme is verified by a numerical example.